Molecular profiling of malignant peripheral nerve sheath tumors associated with neurofibromatosis type 1, based on large-scale real-time RT-PCR - Wolkenstein Pierre; Parfait Béatrice; Bolasco Giulia; Wechsler Janine; Laurendeau Ingrid; Leroy Karen; Vidaud Dominique; Lévy Pascale; Vidaud Michel; Bièche Ivan (Molecular Cancer, 2004)
Abstract Background Neurofibromatosis type 1 (NF1) is an autosomal dominant disorder with a complex range of clinical symptoms. The hallmark of NF1 is the onset of heterogeneous (dermal or plexiform) benign neurofibromas. Plexiform neurofibromas can give rise to malignant peripheral nerve sheath tumors (MPNSTs), and the underlying molecular mechanisms are largely unknown. Results To obtain further insight into the molecular pathogenesis of MPNSTs, we used real-time quantitative RT-PCR to quantify the mRNA expression of 489 selected genes in MPNSTs, in comparison with plexiform neurofibromas. The expression of 28 (5.7%) of the 489 genes was significantly different between MPNSTs and plexiform neurofibromas; 16 genes were upregulated and 12 were downregulated in MPNSTs. The altered genes were mainly involved in cell proliferation (MKI67, TOP2A, CCNE2), senescence (TERT, TERC), apoptosis (BIRC5/Survivin, TP73) and extracellular matrix remodeling (MMP13, MMP9, TIMP4, ITGB4). More interestingly, other genes were involved in the Ras signaling pathway (RASSF2, HMMR/RHAMM) and the Hedgehog-Gli signaling pathway (DHH, PTCH2). Several of the down-regulated genes were Schwann cell-specific (L1CAM, MPZ, S100B, SOX10, ERBB3) or mast cell-specific (CMA1, TPSB), pointing to a depletion and/or dedifferentiation of Schwann cells and mast cells during malignant transformation of plexiform neurofibromas. Conclusion These data suggest that a limited number of signaling pathways, and particularly the Hedgehog-Gli signaling pathway, may be involved in malignant transformation of plexiform neurofibromas. Some of the relevant genes or their products warrant further investigation as potential therapeutic targets in NF1.